2006
DOI: 10.1007/s00442-006-0510-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of slowly cycling soil phosphorus: major restructuring of soil P fractions over four decades in an aggrading forest

Abstract: Although low solubility and slow cycling control P circulation in a wide range of ecosystems, most studies that evaluate bioavailability of soil P use only indices of short-term supply. The objective here is to quantify changes in P fractions in an Ultisol during the growth of an old-field pine forest from 1957 to 2005, specifically changes with organic P (Po) and with inorganic P (Pi) associated with Fe and Al oxides as well as Ca compounds. Changes in soil P were estimated from archived mineral soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
118
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 51 publications
13
118
6
Order By: Relevance
“…For example, standard conceptual models suggest that much of the soil P in occluded forms is not available to terrestrial plants, yet plants have a number of mechanisms to liberate soil-bound P, including mycorrhizae, root exudation and chelation, and rhizosphere redox changes. These interactions (40), as well as those between N and P (41), have the potential to greatly enhance P availability. However, further research on P cycling and availability will be important to better understand and predict longterm patterns of terrestrial NPP.…”
Section: Resultsmentioning
confidence: 99%
“…For example, standard conceptual models suggest that much of the soil P in occluded forms is not available to terrestrial plants, yet plants have a number of mechanisms to liberate soil-bound P, including mycorrhizae, root exudation and chelation, and rhizosphere redox changes. These interactions (40), as well as those between N and P (41), have the potential to greatly enhance P availability. However, further research on P cycling and availability will be important to better understand and predict longterm patterns of terrestrial NPP.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these results did not differ from the findings by Johnson et al (2003), who found evidence that Hedley-labile P pools in soils appeared to be several times larger than annual requirement of P in humid tropical forests, even though many tropical forests appeared to be P limited (Vitousek, 1984). On the other hand, the sufficient P availability in the soil could be maintained during succession (despite the expected nutrient accumulation in forest biomass during secondary succession, see Brown and Lugo, 1990) by a substantial cycling of Po and Pi from Ca compounds, as suggested by Richter et al (2006). Clearly, a further understanding of P biogeochemical processes in forest soils is required, especially focused on the relationship between operationally defined plant-available P and plant P nutrition.…”
Section: Discussionmentioning
confidence: 95%
“…This fact showed that the labile P forms are mostly organic and that Pinus crops can access these fractions. However, even if these values are lower than those reported in other Pinus cultivation systems (BEKELE et al, 2003;RICHTER et al, 2006), there is no evidence of a response of Pinus to isolated P applications. In soils as that studied, the response to P applications is except just at the beginning of the stand (MORO et al, 2014).…”
Section: Resultsmentioning
confidence: 62%
“…In perennial and forestry crops, the diagnosis of phosphorus (P) availability is more complex, since the longer cycle, the greater is the possibility of buffering of the most labile by the less labile forms. Over the course of time, this Gatiboni et al increases nutrient availability in soils under Pinus stands, as emphasized by RICHTER et al (2006); or in successive crops on unfertilized soil, as pointed out by GATIBONI et al (2007).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation